Peran Komunikasi Bisnis Digital dalam Membangun Kepercayaan Konsumen pada E-Commerce Shopee: Studi Kasus Mahasiswa UIN Raden Fatah Palembang - Widia; Akhwalis Shalihah; Inda Febriani; Rensi Amalia (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This study aims to analyze the role of digital business communication in building consumer trust in e-commerce, specifically on the Shopee platform among students of UIN Raden Fatah Palembang. This study employs a qualitative approach using a case study method to gain an in-depth understanding of consumer experiences and perceptions in online transactions. The data were gathered through in-depth interviews, observations, and documentation involving students who actively use Shopee. The data were then analyzed using a thematic approach to identify patterns of digital communication that influence consumer trust. The results show that digital business communication plays an important role through clarity of product information, seller responsiveness, transaction transparency, and the presence of reviews and ratings. Consumers tend to trust sellers who are communicative and responsive, while also considering other users’ reviews as a basis for purchasing decisions. These findings are supported by studies indicating that communication can increase consumer trust in online transactions (Pamungkas et al., 2024). Another study also explains that effective digital communication strategies can strengthen the relationship between businesses and consumers (Milah & Shihabudin, 2025).